Exponential synchronization of inertial neural network with mixed delays via intermittent pinning control. (3rd October 2021) - Hui, Meng; Yan, Jiefei; Zhang, Jiao; Iu, Herbert Ho‐Ching; Yao, Rui; Bai, Lin
Abstract: This article considers the problem of exponential synchronization of inertial neural networks (INNs) with mixed delays via a novel hybrid control scheme consisting of pinning and periodic intermittent control. Both the discrete delay and distributed delay are taken into account in the network model. Through the proper variable substitution, the original system is transferred into a simply formed differential equation. Meantime, some new sufficient conditions are derived by the Lyapunov stability theory for the exponential synchronization of INNs. Eventually, numerical simulations are given to present the effectiveness of the theoretical method.